Pompeii: From the Survey of Ballistic Impacts Towards the Reconstructions of Roman Artillery (1st Century BC) - Adriana Rossi (Engineering Proceedings, 2025)
This volume brings together the reflections of those who have been committed to building a dialogue around the results achieved (and currently underway) by the research project “Comparative Analysis and Certified Reconstructions for a correct experimental archeology: Roman Scorpions and Ballistae for the Imperial mechanical culture, origin of European identity [...]